208Po populated through EC/β+ decay. (December 2020) - Brunet, M.; Berry, T.A.; Podolyák, Zs.; Carroll, R. J.; Lica, R.; Sotty, Ch.; Andreyev, A. N.; Borge, M. J. G.; Cubiss, J. G.; Fraile, L. M.; Fynbo, H. O. U.; Gamba, E.; et al.
Abstract: The structure of 208 Po resulting from the EC/ β + decay of 208 At was studied at CERN's ISOLDE Decay Station (IDS). The high statistics afforded by the high yield of 208 At and the high efficiency HPGe clusters at the IDS allowed for greater insight into lower intensity transitions and thus significant expansion of the 208 Po level scheme. Furthermore, investigation into the isomeric state yielded a new half life 377(9) ns in addition to uncovering new transitions populating the state.